Prognostic Value of Pre- and Post-Treatment FDG PET/CT Parameters in Small Cell Lung Cancer Patients - Kim, Hyoungwoo (Nucl Med Mol Imaging, 2017)
PURPOSE: To evaluate the prognostic value of PET parameters obtained from pre- and post-treatment FDG PET/CT examinations in patients with SCLC. METHODS: Fifty-nine patients with initially diagnosed SCLC from 2009 to 2014 were included and had chemotherapy and/or concurrent chemoradiotherapy. FDG PET/CT examinations were performed before (PET1) and after (PET2) treatment to evaluate treatment response. A region of interest was placed over the primary lesion and metastatic lymph nodes within the thoracic cavity. PET parameters including change from PET1 to PET2 (Δ in %) were acquired: SUVmax, SUVpeak, MTV2.5, TLG, ΔSUVmax, ΔSUVpeak, ΔMTV and ΔTLG. Patient characteristics including staging, age, sex, LDH and response evaluation by RECIST were surveyed. Statistical analysis was done using Kaplan-Meier method and Cox regression analysis with respect to OS and PFS. RESULTS: The median follow-up was 9.6 months (2.5–80.5 months). 27 patients were LD and 32 were ED. Forty-six patients (78.0%) had died, and median OS was 8.6 months; 51 patients (86%) showed disease progression, and median PFS was 2.5 months. On univariate analysis, patients with ED, high interval change (ΔSUVmax and ΔSUVpeak) and low PET2 parameters showed longer OS and PFS. Multivariate analyses demonstrated that ΔSUVpeak (HR 2.6, P = 0.002) was an independent prognostic factors for OS, and MTV2.5 of PET2 (HR 2.8, P = 0.001), disease stage (HR 2.7, P = 0.003) and RECIST (HR 2.0, P = 0.023) were independent prognostic factors for PFS. CONCLUSIONS: Metabolic and volumetric PET parameters obtained from pre- and post-treatment FDG PET/CT examinations in patients with SCLC have significant prognostic information.